2019
DOI: 10.1002/jimd.12189
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and distribution of 2‐hydroxypropyl‐β‐cyclodextrin following a single intrathecal dose to cats

Abstract: 2-Hydroxypropyl-β-cyclodextrin (HP-β-CD) is an experimental therapy for Niemann-Pick disease type C (NPC) that reduced neuronal cholesterol and ganglioside storage, reduced Purkinje cell death, and increased lifespan in npc1−/− mice and NPC1 cats. In this study, tissue distribution was investigated in normal cats that received a single 120-mg dose of [ 14 C]-HP-β-CD (approximately 200 μCi/cat) via the cerebellomedullary cistern (CBMC) and lumbar cistern. One cat was euthanized at each of various time points up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The translatability and effectiveness of the intrathecal administration route have been demonstrated in larger animals (82,83) and in human trials (NCT03381729, NCT02362438), which showed effects in nerves distal to the injection site, including transduction of SCs in the tibial nerve of dogs after intrathecal injection of AAV9 (83). Another route of administration that could be easily translated to the clinic is intravenous injections.…”
Section: Discussionmentioning
confidence: 99%
“…The translatability and effectiveness of the intrathecal administration route have been demonstrated in larger animals (82,83) and in human trials (NCT03381729, NCT02362438), which showed effects in nerves distal to the injection site, including transduction of SCs in the tibial nerve of dogs after intrathecal injection of AAV9 (83). Another route of administration that could be easily translated to the clinic is intravenous injections.…”
Section: Discussionmentioning
confidence: 99%
“…A first study using intra-peritoneal or intra-thecal injection in NPC1-deficient mice failed to show a positive effect [362]. However, subsequent reports revealed that CD prolongs the life span, slows down neurologic disease progression, and halts the degeneration of Purkinje cells in the mouse and cat model [177][178][179][180][181]363,364]. Intra-thecal injections were required, as CD cannot pass the blood-brain barrier [365].…”
Section: Models Mattering For Therapy Developmentmentioning
confidence: 99%
“…Research showed that the hydrophobic inner cavity of HP-β-CD could form an inclusion compound with intracellular accumulated lipids, which could promote lipid efflux, and regulated intracellular lipid homeostasis [12]. Studies in various animal models had demonstrated that HP-β-CD could reduce neuron cholesterol and ganglioside storage and had the potential to treat Niemann-Pick Type C disease (NPC) [13][14][15][16]. HP-β-CD could reduce the levels of membrane cholesterol and Aβ42 in N2a cells by reducing the enzymatic hydrolysis of amyloid precursor protein (APP), becoming a new strategy for treating Alzheimer's disease (AD) [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%